Rapidly fabricating a large area nanotip microstructure for high-sensitivity SERS applications. Issue 42 (16th October 2019) - Ma, Jing; Liu, Wen; Ma, Zhe; Song, Peishuai; Zhao, Yongqiang; Yang, Fuhua; Wang, Xiaodong
Abstract : An easily fabricated novel nanotip microstructure coated with Ag nanoparticles presented a high enhancement factor and high sensitivity. Abstract : Here, we propose a novel nanotip microstructure which can be easily fabricated through a simply Reactive Ion Etching (RIE) process combined with anodic aluminum oxide (AAO) membranes. When combined with Ag coating and annealing on the surface of micro-sized nanotip arrays, the as-formed Ag-nanoparticles (Ag-NPs)/Si-nanotip hybrid structure exhibited a significantly high enhancement factor and highly sensitive surface enhanced Raman scattering (SERS) for rhodamine 6G molecules. The nanotip microstructure showed a sharp curvature with an apex diameter which significantly affected the SERS results. The Ag-NPs/Si-nanotip hybrid structure verified a very prominent "hot spot" effect that exists around the nanotip structures, which contributed mainly to an enhanced SERS signal with an enhancement factor (EF) of 1.6 × 10 6 . Moreover, the Ag-NPs/Si-nanotip hybrid structure demonstrated superior sensitivity, with obvious featured Raman peaks even when the concentration was as low as 10 −10 M. Our work demonstrated a feasible way to prepare a novel nanotip microstructure with a highly localized surface plasmon resonance response which could be feasibly applied for highly sensitive and reproducible SERS applications.